Status of Seagrass Beds in the Waters around Bahowo, Tongkaina Village, Manado City North Sulawesi Province - Togolo, Festy; Menajang, Febry S. I; Manginsela, Fransine B; Kondoy, Khristin I. F; Lasabuda, Ridwan; Schaduw, Joshian N (Jurnal Ilmiah Platax, 2023)
This research was conducted in November 2021 in the waters around Bahowo, Tongkaina Village, Manado City, North Sulawesi Province. Seagrass sampling was carried out using a random sampling method (randomly) with a quadratic transect drawn perpendicular to the shoreline. Thus, 6 species of seagrass were obtained, namely Enhalus acoroides, Halophila ovalis, Thalassodendron ciliatum, Thalassia hemprichii, Syringodium isoetifolium and Halodule pinifolia, with various aquatic environmental conditions. The results of the analysis of the status of the seagrass beds obtained that the seagrass cover value was 50.20% which was included in the "moderate" category, while the seagrass cover per species was Thalassia hemprichii species with the highest cover found was 30.08%, Enhalus acoroides was 21.49% , Halophila ovalis was 6.84%, Thalassodendron ciliatum was 17.39%, Syringodium isoetifolium was 12.31% and Halodule pinifolia was the least common type was 2.35%. The density value of Enhalus acoroides seagrass is 48.375 ind/m2, Halophila ovalis is 14.5 ind/m2, Thalassodendron ciliatum is 35,475 ind/m2, Thalassia hemprichii species with the highest density is 67.25 ind/m2, Syringodium isoetifolium is 27.875 ind/m2 and Halodule pinifolia species density is at least 5.25 ind/m2. The status of the seagrass beds was categorized as "unhealthy" with an average seagrass cover value of 50.20%.Keywords: Seagrass Status, Cover, Seagrass, BahowoÂ ABSTRAKPenelitian ini dilaksanakan pada bulan November 2021 di Perairan Sekitar Bahowo, Kelurahan Tongkaina, Kota Manado, Provinsi Sulawesi Utara. Pengambilan sampel lamun dilakukan menggunakan metode random sampling (secara acak) dengan transek kuadrat yang ditarik tegak lurus garis pantai. sehingga diperoleh 6 jenis lamun yaitu Enhalus acoroides, Halophila ovalis, Thalassodendron ciliatum, Thalassia hemprichii, Syringodium isoetifolium dan Halodule pinifolia, dengan kondisi lingkungan perairan yang beragam. Hasil dari analisis status padang lamun diperoleh nilai tutupan lamun adalah 50,20% termasuk ke dalam kategori â€œsedangâ€, sedangkan tutupan lamun per jenis yaitu Thalassia hemprichii jenis dengan tutupan yang tertinggi dijumpai adalah 30,08%, Enhalus acoroides adalah 21,49%, Halophila ovalis adalah 6,84%, Thalassodendron ciliatum adalah 17,39%, Syringodium isoetifolium adalah 12,31% dan Halodule pinifolia jenis yang paling sedikit ditemukan adalah 2,35%. Nilai kerapatan lamun Enhalus acoroides adalah 48,375 ind/m2, Halophila ovalis adalah 14,5 ind/m2, Thalassodendron ciliatum adalah 35,475 ind/m2, Thalassia hemprichii jenis kerapatannya paling tinggi adalah 67,25 ind/m2, Syringodium isoetifolium adalah 27,875 ind/m2 dan Halodule pinifolia jenis kerapatannya paling sedikit adalah 5,25 ind/m2. Status padang lamun dikategorikan dalam kondisi â€œkurang sehatâ€ dengan nilai rata-rata penutupan lamun adalah 50,20%.Â Â Kata kunci: Status Padang Lamun, Tutupan, Lamun, Bahowo